Implementation of peer support for people with severe mental health conditions in high-, middle- and low-income-countries: a theory of change approach - Hiltensperger, Ramona; Ryan, Grace; Ben-Dor, Inbar Adler; Charles, Ashleigh; Epple, Ellen; Kalha, Jasmine; Korde, Palak; Kotera, Yasuhiro; Mpango, Richard; Moran, Galia; Mueller-Stierlin, Annabel Sandra; Nixdorf, Rebecca; et al. (BioMed Central Ltd, 2024)
Abstract Background Stakeholder engagement is essential to the design, implementation and evaluation of complex mental health interventions like peer support. Theory of Change (ToC) is commonly used in global health research to help structure and promote stakeholder engagement throughout the project cycle. Stakeholder insights are especially important in the context of a multi-site trial, in which an intervention may need to be adapted for implementation across very different settings while maintaining fidelity to a core model. This paper describes the development of a ToC for a peer support intervention to be delivered to people with severe mental health conditions in five countries as part of the UPSIDES trial. Methods One hundred thirty-four stakeholders from diverse backgrounds participated in a total of 17 workshops carried out at six UPSIDES implementing sites across high-, middle- and low-income settings (one site each in India, Israel, Uganda and Tanzania; two sites in Germany). The initial ToC maps created by stakeholders at each site were integrated into a cross-site ToC map, which was then revised to incorporate additional insights from the academic literature and updated iteratively through multiple rounds of feedback provided by the implementers. Results The final ToC map divides the implementation of the UPSIDES peer support intervention into three main stages: preparation, implementation, and sustainability. The map also identifies three levels of actors involved in peer support: individuals (service users and peer support workers), organisations (and their staff members), and the public. In the UPSIDES trial, the ToC map proved especially helpful in characterising and distinguishing between (a) common features of peer support, (b) shared approaches to implementation and (c) informing adaptations to peer support or implementation to account for contextual differences. Conclusions UPSIDES is the first project to develop a multi-national ToC for a mental health peer support intervention. Stakeholder engagement in the ToC process helped to improve the cultural and contextual appropriateness of a complex intervention and ensure equivalence across sites for the purposes of a multi-site trial. It may serve as a blueprint for implementing similar interventions with a focus on recovery and social inclusion among people with mental ill-health across diverse settings. Trial registration ISRCTN26008944 (Registration Date: 30/10/2019).
Keywords: Peer support, Theory of change, Global mental health, Complex interventions, Implementation